STRATEGI PEMASARAN UMKM DI ERA NEW NORMAL - Sriayu Aritha Panggabean (KOLONI, 2022)
The development of advanced technology requires all to adjust from traditional ways to digital-based ways. This pandemic that has not ended has forced humans to be friendly with technology, as well as in the marketing segmentation of UMKM. This study aims to describe the marketing strategy of UMKM in the new normal era. This research uses descriptive qualitative techniques using literature study analysis. Marketing strategies in the new normal era are activating online shops, maximizing the ability of human resources regarding IT, and promoting through the millennial generation. Keywords: Marketing Strategy, UMKM, New Normal